The comparison between Bayesian belief network and traditional methodology of project risk management in large project: evidence from Chinese high-speed train manufacturer - LIU, JING (2010)
This paper consider the comparison between traditional risk management methods (PRINCE2 and BS 6079-3: 2000) and Bayesian belief network according to evidence of China South Locomotive & Rolling Stock Corporation Limited (CSR) Sifang locomotive and rolling stock Co., LTD., meanwhile, consider the project conditions of it and carried on deep research in the risk management method. This paper investigated a sample of 37 responders who work about risk management to test the advantages and disadvantages of traditional risk management methods (PRINCE2 and BS 6079-3: 2000) and Bayesian belief network. The questionnaire method was used and the feedback collected with high quality. The findings and analysis of the research result will complement the primary research and benefit for the literature of project risk management.